Peculiar features of competitive activity of qualified wheelchair basketball players - Grashchenkova, Z.; Mishyn, M.; Okopny, A.; Pityn, M.; Hnatchuk, Y. (Journal of Physical Education and Sport, 2018)
In wheelchair basketball, competitive activity is of complex character that is stipulated by players having different degrees of malfunctions of musculoskeletal system. Despite universalisation of technical and tactical actions in present-day basketball, players of different positions have different manners of running competitive activity and have different efficiency of competitive activity. Aim of research is to analyze peculiarities of competitive activity of qualified athletes in wheelchair basketball. Organization. The research was done in two stages. At the first stage, we analyzed technical and tactical actions of 189 athletes (including 47 athletes of 1-1.5 functional class, 41 athletes of 2-2.5 functional class, 46 athletes of 3-3.5 functional class, 55 athletes of 4-4.5 functional class) listed in official statistics protocols of Men`s World Championship games organized by International Wheelchair Basketball Federation. Results. The most effective means related to handling a basketball wheelchair for players of all functional classes are actions done with two hands: pushing a wheelchair forward with both hands simultaneously, executing a stop with two hands (107 - 138 times), turns in motion done with two hands (112- 130 times), turns on the spot done by both hands (84 - 103 times). Use of other elements of basketball wheelchair handling technique is also rather important. It is related to the fact that players must master new range of required auxiliary actions when handling a basketball wheelchair, which will correspond to the volume of actions of each player. Increase o the number of motion actions related to handling a basketball wheelchair with one hand, allows increase of efficiency of technical actions with the ball. Quick and accurate execution of motion actions, ability to choose the most rational means of execution, and broadening of the range and variability of methods of handling a basketball wheelchair allows versatile use of a player`s individual abilities and increase of athletes` professional growth.